Aging of solid ⁴He under torsional oscillation at low temperatures - Gumann, P.; Kojima, H. (Физика низких температур, 2013)
Observations have been made to reveal unusual aging behavior in solid ⁴He samples contained in a torsional oscillator. Oscillation of samples is initiated at a given oscillator drive amplitude near 100 mK. After the samples are cooled to a measurement temperature, they are “aged” for a waiting time, tw, between 15 min and 25 h. The drive amplitude is then halved and subsequent variation in the oscillator response amplitude, A(t), and frequency are monitored as time t elapses. When the measurement temperature is lower than Ts = 40 mK, A(t) shows un-usual behavior: A(t) initially undershoots to less than half of the original value, partially recovers exponentially and eventually continues to increase logarithmically. The amount of undershoot, partial recovery magnitude and the rate of logarithmic increase all show aging effect with logarithmic dependence on tw. When the measurement temperature is greater than Ts, the above unusual behavior in A(t) disappears. If solid ⁴He cooled below Ts be-haved analogously to spin glasses, A(t/tw) would be independent of tw. Such behavior of A(t/tw) is not observed. Origin of the unusual aging behavior in solid ⁴He is not yet clear. Motion of dislocation lines is discussed as a possible origin.